The impact of mergers on credit union service provision - Fried, Harold O.; Lovell, C.A.Knox; Yaisawarng, Suthathip (Journal of Banking & Finance, 1999)
In this paper we conduct an empirical exercise in which we attempt to provide answers to three questions concerning credit union mergers: (i) do members of acquiring credit unions benefit from mergers?; (ii) do members of acquired credit unions benefit from mergers?; and (iii) what are the characteristics of relatively successful, and relatively unsuccessful, mergers? Our empirical exercise is based on annual samples of nearly 6000 credit unions, including nearly 300 merger participants, during the 1988–1995 period. We find member service provision to have improved in acquired credit unions, and to have been unchanged in acquiring credit unions. We also provide three separate analyses, from three different perspectives, of the role of various characteristics of merging credit unions in determining the success of mergers.